KOMUNIKASI MASSA DAN DEMOKRASI DALAM ARUS SISTEM POLITIK - Puji Laksono (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
The process of mass communication is a reality experienced by society so that it will follow the ideology and political system adopted in the country where it lives. Every country has an ideology that is adhered to as values and principles that serve as guidelines in achieving national ideals. The ideology of a country ultimately determines the political system that is practiced in the life of the nation and state. People who live in a country must be guided by the ideology set. The state ideology becomes the values that are practiced and shared together in daily life, including in the process of mass communication. In the current political mass communication system it should have the potential to become the fourth power and pillar of democracy in a country's political system. Namely the mass media that play an important role as the fourth estate. The process of mass communication takes place in the flow of the country's political system, seen from the perspective of the Four Theories of the Pres and Three Models of Media and Politics, democracy can develop according to the theory of libertarian theory and social responsibility in the four theories of the press, as well as liberal and corporate democracy in the three models of media and politics. Which is the important role of the mass media as the fourth estate can be realized. Whereas in a country that adheres to a media and political system according to authoritarian theory, the soviet communist theory and the pluralist pluralist model are not possible. Although the process of mass communication can play its role as the fourth estate in the realm of democracy, but there are serious challenges that must be faced, namely media conglomeration.